2007
DOI: 10.1002/esp.1493
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term landscape evolution: linking tectonics and surface processes

Abstract: Research in landscape evolution over millions to tens of millions of years slowed considerably in the mid-20th century, when Davisian and other approaches to geomorphology were replaced by functional, morphometric and ultimately process-based approaches. Hack's scheme of dynamic equilibrium in landscape evolution was perhaps the major theoretical contribution to long-term landscape evolution between the 1950s and about 1990, but it essentially 'looked back' to Davis for its springboard to a viewpoint contrary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
203
0
19

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(222 citation statements)
references
References 222 publications
(378 reference statements)
0
203
0
19
Order By: Relevance
“…Kirkby, 1971, 1995. Recent reviews of mathematical landscape evolution models (LEMs) can be found in Coulthard (2001), Willgoose (2005), Codilean et al (2006), Bishop (2007), and Tucker and Hancock (submitted for publication).…”
Section: Introductionmentioning
confidence: 99%
“…Kirkby, 1971, 1995. Recent reviews of mathematical landscape evolution models (LEMs) can be found in Coulthard (2001), Willgoose (2005), Codilean et al (2006), Bishop (2007), and Tucker and Hancock (submitted for publication).…”
Section: Introductionmentioning
confidence: 99%
“…While Thornbury (1969, p 29) argues, "Little of the earth's topography is older than Tertiary and most of it is no older than the Pleistocene" Bishop (2007) claims the Thornbury conclusion is based on "measured erosion rates that were almost certainly too high because of anthropogenic disturbance" and even "when more 'reasonable' long-term erosion rates were used… the Davisian erosion cycle required between 10 and 25 Myr to run its full course." Newer research approaches to studying landform evolution that replaced the Davis developed erosion cycle models do not challenge the Davis concept that landscapes evolve slowly over long periods of time.…”
Section: Why Is the Davis Uniformitarianism Paradigm Important Today?mentioning
confidence: 99%
“…As one of the primary mechanisms by which landscapes manifest and express changes in external boundary conditions, longitudinal profiles allow us to determine if channel incision exceeds, equals or is less than the influx of material into the drainage basin (Bishop 2007). Traditionally, this has been achieved by classifying longitudinal profiles as either upwardly concave or convex (Tippet and Hovius 2000).…”
Section: Introductionmentioning
confidence: 99%